2018
DOI: 10.3390/s18113960
|View full text |Cite
|
Sign up to set email alerts
|

Roof Shape Classification from LiDAR and Satellite Image Data Fusion Using Supervised Learning

Abstract: Geographic information systems (GIS) provide accurate maps of terrain, roads, waterways, and building footprints and heights. Aircraft, particularly small unmanned aircraft systems (UAS), can exploit this and additional information such as building roof structure to improve navigation accuracy and safely perform contingency landings particularly in urban regions. However, building roof structure is not fully provided in maps. This paper proposes a method to automatically label building roof shape from publicly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 28 publications
0
36
0
5
Order By: Relevance
“…It also predicts the magnitude and pressure distribution of roof in the building based on the free stream turbulent flow conditions. Automatic labeling of roof shape for the building [2] is done from the GIS data. The roof top detection is done by using ROC analysis [3] to estimate the cost of error from the aerial images of building.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…It also predicts the magnitude and pressure distribution of roof in the building based on the free stream turbulent flow conditions. Automatic labeling of roof shape for the building [2] is done from the GIS data. The roof top detection is done by using ROC analysis [3] to estimate the cost of error from the aerial images of building.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…[1] [2][3] [4] [48] [49] [50] The application of GIS in recent study has shown higher potential for better societal benefit. A few of the applications are:…”
Section: Introductionmentioning
confidence: 99%
“…Road or Building Footprint: GIS enables to get the accurate terrain, road maps, waterways and the footprints and heights of buildings. [4][5] [18] [20] Apart from the above application areas, GIS has also been used to provide statistics for flood or cyclone affected area, potholes detection, tracking vehicle and geographical changes. [10][17] [47] In this paper, we are going to study the different aspects of the geographic information system such as land management, roof top analysis, traffic analysis, demographic analysis, watershed analysis, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed framework performs better than state-of-the-art building extraction methods, given its higher values of recall, precision, and intersection over Union (IoU).2 of 33 remote sensing, and is extensively used in various applications, including urban planning, cartographic mapping, and land use analysis [1,2]. The significant progress in sensors and operating platforms has enabled us to acquire remote sensing images and 3D point clouds from cameras or Light Detection And Ranging (LiDAR) equipped in various platforms (e.g., satellite, aerial, and Unmanned Aerial Vehicle (UAV) platforms); thus, the methods based on images and point clouds are commonly used to extract buildings [3][4][5].Building extraction can be broadly divided into three categories according to data source: 2D image-based methods, 3D point cloud-based methods, and 2D and 3D information hybrid methods. 2D image-based building extraction consists of two stages, namely, building segmentation and regularization.…”
mentioning
confidence: 99%
“…2 of 33 remote sensing, and is extensively used in various applications, including urban planning, cartographic mapping, and land use analysis [1,2]. The significant progress in sensors and operating platforms has enabled us to acquire remote sensing images and 3D point clouds from cameras or Light Detection And Ranging (LiDAR) equipped in various platforms (e.g., satellite, aerial, and Unmanned Aerial Vehicle (UAV) platforms); thus, the methods based on images and point clouds are commonly used to extract buildings [3][4][5].…”
mentioning
confidence: 99%